Postharvest quality of apples from ‘Maxi Gala’ trees grafted on different rootstocks - Martin, Mariuccia Schlichting de (2022)
This study analyzed the effect of rootstocks G.213, M.9 and Marubakaido with M.9 interstem of 30 and 20 cm (MB/M.9-30cm and MB/M.9-20cm) on postharvest quality, mineral composition and functional properties of 'Maxi Gala' apples. The evaluations was performed using fruits from a commercial orchard located in Vacaria, RS, Brazil. Fruits were stored for 135 and 147 days in the 2014/2015 and 2015/2016 seasons, respectively, and analyzed one day after harvest and after cold storage (1.0±0.2 °C) followed by seven days in ambient condition. The mineral composition of fruits showed small and inconsistent differences between rootstocks. The MB/M.9-20cm provided higher total antioxidant activity and levels of total phenolic compounds in fruit peel than MB/M.9-30cm. For 2014/2015 season, soluble solids content at harvest was higher in fruits from trees with G.213 rootstock, not differing only from MB/M.9-30cm. In 2015/2016 season, G.213 and M.9 provided higher soluble solids content after storage compared to MB/M.9-30 cm and MB/M.9-20cm. G.213 rootstock anticipated fruit maturity compared to M.9 in 2014/2015 season. Other quality attributes of ‘Maxi Gala’ apples, at harvest and after cold storage, were similar between rootstocks G.213, M.9 and Maruba with M.9 interstem of 30 and 20cm.